1994
DOI: 10.1007/bf01730363
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence rates of gallstone disease in Italy

Abstract: The prevalence of gallstone disease and associated factors in the entire population of subjects aged 15-65 years born and resident in Chianciano Terme (Siena - Tuscany) was examined in the years 1985 and 1986. The investigation included gallbladder ultrasonography, administration of a questionnaire on personal and family history, physical examination and blood chemistry. A total of 1809 subjects (attendance rate 87.7%) participated in the study. Personal history and physical examination showed that Chianciano … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 45 publications
4
24
3
Order By: Relevance
“…Epidemiological data have revealed that in the general population, the overall prevalence range of gallstones is 3.29%-14.85% (10)(11)(12)(13), and the overall prevalence range of NAFLD is 14%-40%. The pooled prevalence of GD in the NAFLD group in the present meta-analysis was 17%, which is higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological data have revealed that in the general population, the overall prevalence range of gallstones is 3.29%-14.85% (10)(11)(12)(13), and the overall prevalence range of NAFLD is 14%-40%. The pooled prevalence of GD in the NAFLD group in the present meta-analysis was 17%, which is higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The overall prevalence of gallstones is approximately 3.29%-14.85% in the general population (10)(11)(12)(13). Increased age, female sex, obesity, metabolic syndrome, hypertriglyceridemia, diabetes and insulin resistance are major risk factors for gallstones (10,14).…”
Section: Introductionmentioning
confidence: 99%
“…The sonographers were unaware of the participant's clinical and laboratory characteristics. Gallstones were present if the gallbladder contained echoes that moved with gravity except when the stones were large, a septum existed in the gallbladder or there was an enclosed infundibulum [12] . Cholelithiasis was defined as previous history of cholecystectomy or current, sonographically diagnosed gallstones.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, because obese individuals are more likely than normal weight individuals to acquire cholelithiasis (6,7), obesity is generally recognized as a major ChGS risk factor (3)(4)(5)(6)(7). Nonetheless, close association clinically and pathophysiologically between the two diseases is often inconsistent (3,8,9). For example, two important indicators of cholelithiasis risk, the cholesterol saturation index (CSI) of gallbladder bile and the speed and completeness of gallbladder emptying, display considerable intersubject variation among obese patients (10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%